Infrared multiphoton dissociation of SiF4: Gas phase reactions of SiF3 with F and H2 - Alcaraz, A. N. (2004)
The infrared multiphoton dissociation (IRMPD) of pure SiF4 and in mixtures with different gases was studied using a tunable CO2 TEA laser. The initial dissociation step of the IRMPD of SiF4 was found to be the decomposition into SiF3 and F. The gas phase reactions of trifluorosilyl, SiF3, with F and H2 was investigated. A kinetic scheme was proposed to explain the experimental results. The set of coupled differential equations associated to this scheme was numerically solved. The rate constants of the SiF3+F→SiF4 and SiF3+H 2→SiF3H+H reactions were determined.